PENGARUH BERBAGAI MACAM WARNA PENCAHAYAAN TERHADAP PERFORMA AYAM PEJANTAN PADA FASE STARTER: EFFECT OF VARIOUS LIGHTING COLORS ON THE PERFORMANCE OF MALE CHICKEN IN THE STARTER PHASE - Purnama, Ardy; Wulandari, Eudia Christina; Abdurrahman, Zakaria Husein (Tropical Animal Science, 2024)
This research aims to determine the effect of various lighting colours on the performance of male chickens in the starter phase/1-10 days old. The experimental design used in this study was a completely randomized design (CRD) with 6 treatments and 4 replications. Each replicate (test unit) uses 4 chickens. Parameters observed were ration consumption, daily body weight gain, body weight gain, feed conversion and mortality. The results of the research that has been carried out are that the effect of various lighting colours on starter phase bulls has no significant effect (P>0.05) on ration consumption, daily body weight gain (PBBH), body weight gain (PBB), feed conversion, and mortality. The conclusion from this study is the effect of various lighting colours on the performance of the roosters in the starter phase. It can be concluded that it is not significant, but numerically, the best light weight gain is shown in the T5 treatment, namely the colour of red light.